2016
DOI: 10.15740/has/tajh/11.2/401-407
|View full text |Cite
|
Sign up to set email alerts
|

Resource use efficiency of bitter gourd in Konkan region (M.S.)

Abstract: :Resource use efficiency of production of bitter gourd (Momordica charantia L.) in Konkan region (M.S.) was undertaken with a cross sectional sample of 120 bitter gourd cultivators. The per hectare physical input utilization indicated that, the proportion of family labour days was more (53.50%) than hired labour days (46.00%) with per hectare average of 267.84 labour days. Regarding other inputs Rs.5045.00 of supporting and shading materials, 148.90 kg N, 116.60 kg P 2 O 5 , 19.88 kg K 2 O, 34.58 q FYM, 637.07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…223857 in case of marginal to large farm size respectively. These findings were in conformity with Krishna et al (2021); Kshirsagar et al (2016); Mathew et al (2019).…”
Section: Income Parameterssupporting
confidence: 92%
“…223857 in case of marginal to large farm size respectively. These findings were in conformity with Krishna et al (2021); Kshirsagar et al (2016); Mathew et al (2019).…”
Section: Income Parameterssupporting
confidence: 92%
“…The second most important constraint faced by the cucurbit crop growers was the unavailability of quality seeds (HYV) (overall Garrett score 55. 37). Keeping this in view, there was a strong need to strengthen extension services for providing information regarding technical knowledge and high-yielding variety amongst the cucurbit growers in the study area.…”
Section: Management and Technical Problemsmentioning
confidence: 97%
“…In addition to the above problems, the minor problems faced also lack of awareness about the benefits of the scheme (rank VI), lack of the proper guideline for getting KCC (rank VII),and delay in disbursement of loans (rank VIII). The farmers further ranked IX higher constraints faced by the illiteracy of farmers and observed Garrett's score of 46.83 followed by the hectic documentation constraints faced in the production of cucumber and bitter gourd Garrett's score was45.99 and rank was X [37,38]. Input -Output Ratio a.…”
Section: Financial Problemsmentioning
confidence: 99%
“…The producers' share in consumer's rupee of bitter gourd was 36.85% in PWM. A group researchers have recently shown that the low prices offered by market intermediaries, high transport cost, and multiplicity of market charges have contributed to low producers' share in consumer's rupee of bitter gourd (Kshirsagar et al, 2016). The study revealed that the mean producers' share in consumer's rupee was only 42.16%.…”
Section: Price Spread and Producers' Sharementioning
confidence: 99%